Identifying potential DNA methylation markers for the detection of esophageal cancer in plasma - Pei, Bing; Zhao, Guodong; Geng, Zhixin; Wang, Yue; Wang, Menglin; Wang, Xiaomei; Xiong, Shangmin; Zheng, Minxue (Frontiers in Genetics, 2023)
Background: Esophageal cancer (EC) is a leading cause of cancer-related deaths in China, with the 5-year survival rate reaching less than 30%, because most cases were diagnosed and treated at the advanced stage. However, there is still a lack of low-cost, efficient, and accurate non-invasive methods for the early detection of EC at present. Methods: A total of 48 EC plasma and 101 control plasma samples were collected in a training cohort from 1 January 2021 to 31 December 2021, and seven cancer-related DNA methylation markers (ELMO1, ZNF582, FAM19A4, PAX1, C13orf18, JAM3 and TERT) were tested in these samples to select potential markers. In total, 20 EC, 10 gastric cancer (GC), 10 colorectal cancer (CRC), and 20 control plasma samples were collected in a validation cohort to evaluate the two-gene panel. Results:ZNF582, FAM19A4, JAM3, or TERT methylation in plasma was shown to significantly distinguish EC and control subjects (p < 0.05), and the combination of ZNF582 and FAM19A4 methylation was the two-gene panel that exhibited the best performance for the detection of EC with 60.4% sensitivity (95% CI: 45.3%–73.9%) and 83.2% specificity (95% CI: 74.1%–89.6%) in the training cohort. The performance of this two-gene panel showed no significant difference between different age and gender groups. When the two-gene panel was combined with CEA, the sensitivity for EC detection was further improved to 71.1%. In the validation cohort, the sensitivity of the two-gene panel for detecting EC, GC, and CRC was 60.0%, 30.0%, and 30.0%, respectively, with a specificity of 90.0%. Conclusion: The identified methylation marker panel provided a potential non-invasive strategy for EC detection, but further validation should be performed in more clinical centers.